ENCOURAGING WOMEN LEADERSHIP AND WOMEN EMPOWERMENT IN STATE-OWNED ENTERPRISES’S ENVIRONMENT AS IMPLEMENTATION OF AKHLAK’s CORE VALUE (Proceedings of the World Conference on Women’s Studies, 2023)
Indonesian state-owned companies have the potential to increase Gross Domestic Product by USD 135 billion by 2025 if they can improve the status of gender equality in the world of work. The Ministry of SOEs seeks to increase women's representation in the Board of Commissioners, Management Board and one level below the Management Council, with a target of 15% in 2021 and 25% in 2023. There has also been an increased focus on the representation of young people within the Board of Directors, and below levels, from state-owned enterprises to 5% in 2021 and 10% in 2023. A survey conducted by McKinsey in 2021 on women in the workplace stated that female leaders produce more fruitful results because women are adept at navigating work/life balance, ensuring that the workload is manageable. This paper explores how to encourage women's leadership and how to empower women in MSME business within SOEs. This will achieve better results in MSME business performance, a more conducive and productive work environment and prioritize respect free from gender discrimination to create gender equality and safeguard human rights. The methodused by researchers in this study is descriptive analysis and Analytic Hierarchy Process (AHP). The results obtained in this study are the leadership of women MSME owners who receive higher BUMN support than those who do not receive. While the novelty of this study is the leadership and empowerment of women in MSMEs within State-Owned Enterprises (MSMEs)
Keywords: women in leadership; women empowerment; gender equality; espect in the workplace; Analytic Process Hierarchy; MSMEs